Edukasi Gizi Seimbang sebagai Upaya Penanganan Bayi dan Balita dengan Berat Badan Tidak Naik di Desa Mutihan Sondakan Surakarta - Darah Ifalahma; Ana Yuliana; Adisti Amalya Putri Handayani; Fatimah Eira Yudhayana (Jurnal Informasi Pengabdian Masyarakat, 2026)
Nutritional problems among infants and toddlers remain a significant public health concern because they can affect children's growth, development, and overall quality of life. Malnutrition includes undernutrition, overnutrition, and obesity, all of which may lead to short- and long-term health consequences. One of the early indicators of growth problems is the absence of weight gain in two consecutive weighing periods. This condition is often associated with inadequate energy and protein intake, inappropriate feeding practices, recurrent infectious diseases, and limited parental knowledge regarding balanced nutrition principles. Based on Posyandu data collected in January 2026 in RW 10 Mutihan, 19 toddlers were identified as experiencing no weight gain, alongside several cases of undernutrition, overnutrition, and obesity. These findings indicate the existence of a double burden of malnutrition within the community. To address this issue, balanced nutrition counseling was implemented as a promotive and preventive intervention aimed at improving mothers’ knowledge, encouraging appropriate feeding practices, and supporting regular monitoring of child growth and nutritional status.